1974
DOI: 10.1128/iai.10.6.1260-1265.1974
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Staphylococcal Exfoliative Toxin with Concanavalin A

Abstract: Treatment of mouse embryo fibroblasts (MEF) grown in vitro with purified staphylococcal exfoliative toxin (ET) increased the concanavalin A (Con A) agglutinability of MEF 3.5-fold over control cells. Possible explanations for this phenomenon were investigated. ET lacked proteolytic activity on denatured casein. Con A, however, was found to interact directly with ET as evidenced by the formation of precipitation in an agar gel diffusion plate and in increased turbidity in solution. This interaction was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1975
1975
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
0
9
1
Order By: Relevance
“…The maximum binding detected in our system was in the 30 to 40% range, whereas Brunner and Chanock (2) reported binding of 80% of their labeled mycoplasma antigen. Previously we reported the possibility of the ET being a glycoprotein (18). A possible explanation for the lower binding figures we obtained may be as-cribable to the glycoprotein nature of our antigen.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The maximum binding detected in our system was in the 30 to 40% range, whereas Brunner and Chanock (2) reported binding of 80% of their labeled mycoplasma antigen. Previously we reported the possibility of the ET being a glycoprotein (18). A possible explanation for the lower binding figures we obtained may be as-cribable to the glycoprotein nature of our antigen.…”
Section: Discussionmentioning
confidence: 63%
“…Crude toxin was precipitated from the HIB cultures by addition of aqueous saturated (NH4)2SO4 to a final concentration of 80%. The crude toxin was collected by centrifugation after standing at 4 C for 18 h, dissolved in distilled water, and dialyzed against 0.0015 M phosphate buffer, pH 7.3, to free it of (NH4)2S04. After lyophilization, the crude toxin was electrofocused in a glycerol density gradient with 1% carrier ampholytes (LKB Instruments Inc.), pH 6 to 8, and the fractions between pH 6 and 7 were collected and pooled.…”
Section: Methodsmentioning
confidence: 99%
“…Certain isolation procedures could cause the toxin to complex with other components that would make the toxin appear to have a higher molecular weight. For example, purified preparations of ET, isolated in our laboratory by isoelectric density gradient electrophoresis, were glycoproteins containing 9% carbohydrate (147). B. Wiley (unpublished results) showed that the carbohydrate was not a contaminant from the glycerol density gradient used for electrofocusing.…”
Section: Isolation and Purificationmentioning
confidence: 97%
“…Native ET was also shown to have no intrinsic arylsulfatase, ␤-galactosidase, or cathepsin activity (these enzymes are normally present in lysosomes) (278). The toxins did not have any enzymatic activity toward known nonspecific substrates, including casein (134,218), and using sensitivity plates (15,21), and their activity was unaffected by any of a wide range of metabolic inhibitors tested (24,249). Even attempts at crystallizing either ETA (289) or ETB (180) to determine their three-dimensional structure, which might shed light on their mechanism of action, met with little success because of difficulty in obtaining stable crystals.…”
Section: Putative Mechanism Of Actionmentioning
confidence: 99%